THE RELATIONSHIP BETWEEN SCHOOL ADMINISTRATORS’ AGILE LEADERSHIP AND SCHOOL TEACHERS’ JOB MOTIVATION UNDER THE SUPERVISION OF SAMUTPRAKARN PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Ratanapitakdhada, Chookwan; Kettanom, Thasporn; Jenkwao, Sarisa (Journal of MCU Nakhondhat, 2024)
This research aimed to study 1) The level of school administrators’ agile leadership under the supervision of Samutprakarn Primary Educational Service Area Office 1; 2) The level of job motivation; 3) The relationship between the school administrators’ agile leadership and job motivation; and 4) The guidelines for developing school administrators’ agile leadership to enhance schoolteachers’ job motivation. A mixed-methods research approach was employed. The sample group consists of 306 schoolteachers, selected through stratified random sampling based on school sizes. The research tools used were a 5-point Likert scale questionnaire with a reliability of 0.973 and an interview form. The data were analyzed by using statistics, mean, standard deviation, Pearson correlation coefficients, and content analysis. The results revealed that 1) The overall and individual aspects of agile leadership among school administrators were found to be at a high level; 2) School teachers’ job motivation, both overall and in specific areas, was at a high level; 3) The relationship between the school administrators’ agile leadership and teachers’ job motivation was positive at the very high level at the significance level of .01; 4) The guidelines for developing school administrators’ agile leadership to enhance teachers' job motivation consisted of 4 aspects as follows: 4.1) There were three guidelines for developing context-setting agility in enhancing work itself-related motivation; 4.2) There were six guidelines for developing stakeholder agility in enhancing work itself-related motivation; 4.3) There were seven guidelines for developing creative agility in enhancing work achievement-related motivation; 4.4) There were four guidelines for developing self-leadership agility in enhancing work achievement-related motivation.